2011
DOI: 10.1016/j.ajpath.2010.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Topoisomerase II α Status in Breast Cancer by Quantitative PCR, Gene Expression Microarrays, Immunohistochemistry, and Fluorescence in Situ Hybridization

Abstract: Anthracyclines are frequently used for the treatment of breast cancer and topoisomerase II alpha (TOP2A) is considered to be the molecular target. Numerous studies have evaluated the predictive value of TOP2A using different methodological approaches and inconsistent results have been reported. Indeed, the correlation between techniques for the assessment of TOP2A status has not been well evaluated. In this study, we determined TOP2A status in 61 breast tumor samples by realtime PCR, DNA microarrays, immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 44 publications
5
39
0
5
Order By: Relevance
“…More specifically, highly proliferative subtypes such as triple negative, luminal B, and HER2-enriched expressed higher levels of the enzyme and are associated with poorer prognosis relative to less proliferative subtypes. 12,25 In this study, we focused on TNBC only, which excluded the heterogeneity of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, highly proliferative subtypes such as triple negative, luminal B, and HER2-enriched expressed higher levels of the enzyme and are associated with poorer prognosis relative to less proliferative subtypes. 12,25 In this study, we focused on TNBC only, which excluded the heterogeneity of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies. 7,12,34 Romero et al 12 reported that TOP2A expression in breast cancer was associated with high proliferation and aggressive tumor subtypes. Rody et al 7 found that TOP2A expression showed a strong correlation with tumor size, grading, HER2, and Ki67 expression as well as nodal status.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Outcomes of results both at the level of evaluation of TOP2A as well as at the level of interpretation are extremely different [24][25][26][27][28][29][30][31][32][33]. If biology of breast carcinoma is similar around the world, then methods of TOP2A evaluation, criteria of interpretation and selection of patients are responsible for the differences [34][35][36][37][38][39][40][41]. We put emphasis on criteria of interpretation, and decided to create out own system of We found in our study that cases with positive TOP2A status measured by the IHC method for TOP2A protein presented a statistically significantly better response to therapy which included anthracyclines as one of the chemotherapeutics (AC program in our study) in neoadjuvant therapy measured by relapses (DFS).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms of drug resistance have been examined. Overexpression of a membrane efflux transporter, P-glycoprotein (P-gp) (Shi et al, 2011) (Romero et al, 2011), changes in topoisomerase II activity (Romero et al, 2011), modifications in glutathione S-transferase (Romero et al, 2012), and altered expression of apoptosis-associated protein Bcl-2 (Bjerre et al, 2012;Larsen et al, 2012) and tumor suppressor protein p53 . ERα status, although lesser known, have also been studied in connection with MDR.…”
Section: Introductionmentioning
confidence: 99%